Preparation and piezoelectric light synergistic catalysis application of samarium and cobalt co-doped bismuth ferrite nano material

By co-doping samarium and co-doping bismuth ferrate nanomaterials in bismuth ferrate, the problem of low efficiency in piezoelectric-optical synergistic catalysis has been solved, and the degradation of organic pollution has been significantly improved. Effects of substance and hydrogen production efficiency.

CN119425710APending Publication Date: 2025-02-14HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411563987.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Bismuth ferrate has low efficiency in piezoelectric-optical synergistic catalytic degradation of organic pollutants and hydrogen production, mainly due to its energy band structure and piezoelectric properties.

Method used

By co-doping samarium and cobalt elements into bismuth ferrate, the co-precipitation method is used to prepare samarium and co-doped bismuth ferrate nanomaterials, and their energy band structure and piezoelectric properties are adjusted to improve their piezoelectric-optical synergistic catalysis. performance.

Benefits of technology

The efficiency of piezoelectric and co-doped bismuth ferrate nanomaterials in piezoelectric-optical synergistic catalytic degradation of organic pollutants and hydrogen production is significantly improved. Compared with pure bismuth ferrate, its degradation rate constant k value is increased by 14.36 times, and the hydrogen production efficiency is Increased by 1.73 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005118701800000011
    Figure HDA0005118701800000011
  • Figure HDA0005118701800000012
    Figure HDA0005118701800000012
  • Figure HDA0005118701800000021
    Figure HDA0005118701800000021
Patent Text Reader

Abstract

The invention relates to preparation of a samarium and cobalt co-doped bismuth ferrite nano material and application of the samarium and cobalt co-doped bismuth ferrite nano material in the field of piezoelectric light concerted catalysis. Compared with pure-phase BiFeO3, the samarium and cobalt co-doped bismuth ferrite nano material synthesized by a coprecipitation method shows a remarkably enhanced piezoelectric optical effect. Under the synergistic effect of ultrasound and light, the samarium and cobalt co-doped bismuth ferrite nano material can achieve efficient degradation of rhodamine B and remarkable improvement of hydrogen production efficiency, the degradation rate constant is 14.36 times that of pure-phase BiFeO3, and the hydrogen production efficiency is 1.73 times that of pure-phase bismuth ferrite. By doping the samarium element, the piezoelectric coefficient of bismuth ferrite is improved, and the efficiency of piezoelectric light concerted catalytic reaction is further improved. The cobalt element is doped into the bismuth ferrite, so that the photocatalytic activity of the bismuth ferrite is improved, and the piezoelectric light synergistic catalytic performance of the material is effectively improved. The invention provides a method for improving rhodamine B degradation and water decomposition of the material to generate hydrogen through element doping, and the method has the characteristics of simple process flow and strong operability, and has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] This article belongs to the field of piezoelectric photocatalytic technology, and specifically involves the preparation of a samarium and cobalt co-doped bismuth ferrite nanomaterial and the application of the composite material in piezoelectric photocatalytic degradation of pollutants and hydrogen production. Background technology:

[0003] As a sustainable energy source, solar energy is inexhaustible. Photocatalytic treatment of sewage using solar energy is an efficient, economical and environmentally friendly remediation technology that has been widely recognized. However, its efficiency is still not ideal, which has become a key factor restricting its widespread application. Recent studies have found that the intrinsic driving force of semiconductor photocatalysis can be effectively enhanced by introducing external stimuli such as temperature changes, mechanical vibrations and magnetic fields. Piezoelectric catalysis technology, as an emerging energy conversion method, can achieve catalytic reactions through charge separation generated by piezoelectric materials under mechanical stress. This technology has the advantages of no need for external power supply and mild reaction conditions, and is suitable for application in multiple fields such as energy, environmental protection and chemical synthesis. Piezoelectric photocatalytic technology combines the dual advantages of piezoelectric catalysis and photocatalysis, and has the characteristics of improving catalytic efficiency, using natural energy such as solar energy and mechanical energy at the same time, reducing catalyst costs, enhancing stability, reducing environmental impact and strong flexibility. Therefore, piezoelectric photocatalytic technology is gradually receiving widespread attention, providing an effective way to solve environmental pollution and energy shortages, and has broad development prospects. At present, the mechanism research of piezoelectric catalytic technology mainly focuses on two categories: band theory and screening charge effect. The band theory originated in the field of photocatalysis. The piezoelectric potential generated by piezoelectric materials is used to adjust the band structure to control the flow of internal carriers to the catalyst surface, thereby promoting the separation of carriers and accelerating the redox reaction. The screening charge effect believes that the charges involved in the redox reaction do not come from the inside of the material, but from the screening charges adsorbed on the surface of the external system.

[0004] Bismuth ferrite (BFO), as a room temperature multiferroic material, has broad application prospects in spintronic devices and ferroelectric storage. In addition, it is also a photocatalyst with photosensitivity and weak magnetism, and has potential value in the field of photocatalytic degradation of organic pollutants and water treatment. As a solar-driven p-type semiconductor, bismuth ferrite has a perovskite structure with a distorted R3c space group, and has the advantages of visible light absorbance (band gap of 2.1-2.7 eV), non-toxicity, low cost, chemical stability, and intrinsic polarization field.

[0005] The appropriate amount of ion doping can effectively adjust the bandgap width and reduce the recombination rate of photogenerated carriers, thereby improving the photocatalytic performance of the sample. Transition metal ions have variable valence due to the presence of unpaired electrons in their d orbitals, so they can be used as capture sites for photogenerated electrons and holes, effectively separating photogenerated electrons and holes, and prolonging their recombination time, which is beneficial to improving photocatalytic performance. By doping with rare earth metals and transition metal ions, the band gap of bismuth ferrite can be reduced, the absorption spectrum can be red-shifted, and the absorption capacity of bismuth ferrite to visible light can be improved. Summary of the invention:

[0006] The present invention aims to solve the problem that the piezoelectric photocatalytic degradation of organic pollutants and the piezoelectric photocatalytic hydrogen production efficiency are low due to the energy band structure of bismuth ferrite and the piezoelectric photocatalytic performance of bismuth ferrite. At present, rare earth element and transition metal doping is one of the main methods for modifying bismuth ferrite to improve material performance. Rare earth element and transition metal doping can lead to the improvement of the piezoelectric performance of bismuth ferrite, adjust the band gap width of bismuth ferrite, and improve the absorption capacity of bismuth ferrite to visible light, thereby enhancing the piezoelectric photocatalytic ability of bismuth ferrite.

[0007] The present invention discloses a preparation method and piezoelectric-photocatalytic application of samarium-cobalt co-doped bismuth ferrite nanomaterial, which mainly involves the preparation and characterization of samarium-cobalt co-doped bismuth ferrite nanomaterial, and the research on the piezoelectric-photocatalytic degradation of organic pollutants and hydrogen production of the nanomaterial, which is specifically carried out by the following steps:

[0008] Step 1: dissolving bismuth nitrate, iron nitrate, samarium nitrate and cobalt nitrate in a dilute nitric acid solution, and ultrasonicating to form a uniform transparent colorless solution; then adjusting the pH value to make the solution alkaline, centrifuging the solution to obtain a precipitate, and drying to obtain a certain amount of solid;

[0009] Step 2: Grind the solid obtained in step 1, and place the ground powder into a tube furnace for calcination in air to obtain a calcined solid powder;

[0010] Step 3: The solid powder calcined in step 2 is acid-washed and water-washed, centrifuged, alternately three times, and finally washed with ethanol, and vacuum-dried to obtain samarium and cobalt co-doped bismuth ferrite nanoparticles.

[0011] The molar ratio of bismuth nitrate to samarium nitrate in step 1 is 0.8:0.1 to 0.95:0.05, preferably 0.9:0.1. The molar ratio of ferric nitrate to cobalt nitrate is 0.8:0.1 to 0.95:0.05, preferably 0.9:0.1.

[0012] The dilute nitric acid solution described in step 1 is prepared by mixing concentrated nitric acid and water in a volume ratio of 1:30 to 40.

[0013] The pH value in step 1 is alkaline and is between 9 and 10, preferably 9.8.

[0014] The drying conditions in step 1 are: temperature of 50-70° C., preferably 60° C.; time of 9-14 h, preferably 12 h.

[0015] The heating rate in step 2 is 4-8°C / min, preferably 5°C / min.

[0016] The calcination temperature in step 2 is first raised to 300° C. and maintained for 30 to 60 minutes, preferably 40 minutes, and then raised to 500° C. and maintained for 40 to 120 minutes, preferably 60 minutes.

[0017] The centrifugal speed described in step 3 is 9000r / min.

[0018] The vacuum drying conditions described in step three are: temperature of 50-70°C, preferably 60°C; vacuum degree of -25--30kPa, preferably -30kPa; time of 9-14h, preferably 12h.

[0019] Step 4. Application of samarium and cobalt co-doped bismuth ferrite nanomaterials in piezoelectric-photocatalytic degradation of organic pollutants. The specific operation steps are as follows: uniformly disperse the samarium and cobalt co-doped bismuth ferrite nanomaterials in an aqueous solution of the organic pollutant Rhodamine B, measure the absorbance change of the Rhodamine B aqueous solution under the conditions of mechanical force and light by a liquid UV-visible spectrophotometer, and finally calculate the degradation rate of the Rhodamine B aqueous solution.

[0020] Step 5: Application of samarium and cobalt co-doped bismuth ferrite nanomaterials in piezoelectric photocatalytic decomposition of water to produce hydrogen. The specific steps are as follows: first, the samarium and cobalt co-doped bismuth ferrite nanomaterials are evenly dispersed in a methanol aqueous solution, and then the mixed solution is poured into a sealed container, and then nitrogen is introduced to remove the air in the system. Next, under the combined action of mechanical force and light, the amount of hydrogen produced is measured by gas chromatograph.

[0021] The concentration of the Rhodamine B (RhB) solution in step 4 is 5 mg / L.

[0022] The mechanical force and light described in steps 4 and 5 are specifically generated by the following method: subjecting the reaction solution containing samarium and cobalt co-doped bismuth ferrite nanomaterials to ultrasound and xenon lamp irradiation.

[0023] Preferably, the ultrasonic frequency is 20-60 kHz, more preferably 40 kHz; the xenon lamp power is 100-500 W, preferably 300 W, and the filter is λ>420 nm.

[0024] The present invention characterizes the samarium and cobalt co-doped bismuth ferrite nanomaterial by means of an X-ray powder diffractometer, a scanning electron microscope, a fluorescence spectrometer, and an ultraviolet-visible spectrophotometer, and tests its piezoelectric photocatalytic degradation performance and hydrogen production performance by means of an ultraviolet-visible spectrophotometer and a gas chromatograph.

[0025] Advantages and effects of the present invention:

[0026] The embodiment of the present invention discloses a method for preparing a samarium and cobalt co-doped bismuth ferrite nanomaterial and its application in the field of piezoelectric photocatalysis. The present invention adopts a simple coprecipitation method to co-dope samarium and cobalt elements into bismuth ferrite, thereby enhancing its visible light absorption and narrowing its energy band. Under the condition of applying ultrasound, the energy band of the samarium and cobalt co-doped bismuth ferrite nanomaterial will tilt, further improving the piezoelectric photocatalytic performance.

[0027] Specifically, the advantages of the present invention are: by co-doping samarium and cobalt elements, the piezoelectric coefficient of bismuth ferrite is increased, thereby improving the efficiency of the piezoelectric photocatalytic reaction; the cobalt element is doped into bismuth ferrite to improve the photocatalytic activity of bismuth ferrite; the samarium element is doped into bismuth ferrite to improve the piezoelectric catalytic performance of bismuth ferrite. By co-doping samarium and cobalt elements, bismuth ferrite can inherit the common advantages of the two elements after doping, enhance its visible light absorption, significantly improve the degradation of pollutants Rhodamine B and improve hydrogen production efficiency; the preparation method of the present invention is simple, the materials are easy to obtain, and the cost is low, which is conducive to industrial production. Experimental results show that the rate constant k value of samarium and cobalt co-doped bismuth ferrite nanomaterials in the degradation of Rhodamine B is 14.36 times that of pure phase bismuth ferrite; in terms of synergistic hydrogen production, its effect is 1.73 times that of pure phase bismuth ferrite. Therefore, the present invention has broad application prospects. Description of the drawings:

[0028] Figure 1 X-ray powder diffraction patterns of samarium and cobalt co-doped bismuth ferrite nanomaterials and bismuth ferrite nanomaterials

[0029] Figure 2 Scanning electron microscope image of samarium and cobalt co-doped bismuth ferrite nanomaterials

[0030] Figure 3 Fluorescence spectra of samarium and cobalt co-doped bismuth ferrite nanomaterials and bismuth ferrite nanomaterials

[0031] Figure 4 Solid UV-visible diffuse reflectance absorption spectra of samarium and cobalt co-doped bismuth ferrite nanomaterials and bismuth ferrite nanomaterials

[0032] Figure 5 The dotted line graph shows the comparison of piezoelectric catalytic degradation rate of bismuth ferrite nanomaterials co-doped with samarium and cobalt in different proportions

[0033] Figure 6 The dot-line graph shows the comparison of piezoelectric photocatalytic degradation rate of samarium and cobalt co-doped bismuth ferrite nanomaterials and their control group

[0034] Figure 7 Comparison of hydrogen production between samarium and cobalt co-doped bismuth ferrite nanomaterials and bismuth ferrite nanomaterials Specific implementation method:

[0035] Implementation 1:

[0036] Step 1, dissolving 0.4802 g of bismuth nitrate pentahydrate, 0.3232 g of ferric nitrate nonahydrate, 0.0489 g of samarium nitrate hexahydrate and 0.0582 g of cobalt nitrate hexahydrate in 33 ml of dilute nitric acid solution, forming a uniform transparent colorless solution by ultrasonic treatment, then adjusting the pH value of the solution to 9.8, centrifuging and placing in a drying oven, drying at 60° C. for 12 hours to obtain a solid powder;

[0037] Step 2: After the solid is completely dried and cooled to room temperature, grind it into powder using a mortar. Then put the powder into a tube furnace, heat it to 300°C at a heating rate of 5°C / min, and calcine for 40 minutes; then heat it to 500°C and calcine for 60 minutes to obtain the calcined powder;

[0038] Step 3, washing the calcined powder three times with dilute nitric acid and deionized water alternately by centrifugation, washing twice with anhydrous ethanol, and finally drying under vacuum at 60° C. for 12 hours to obtain samarium- and cobalt-co-doped bismuth ferrite nanoparticles doped with 10% samarium and 20% cobalt;

[0039] Step 4: Weigh 25 mg of the samarium and cobalt co-doped bismuth ferrite nanoparticles obtained above, and evenly disperse them into 25 ml of a 5 mg / L rhodamine B solution. Under ultrasonic vibration and illumination conditions, measure the absorbance change of the rhodamine B solution by a UV-visible spectrophotometer every 10 minutes starting from the 0th minute, and continue measuring for 60 minutes;

[0040] Step 5. Take 10 mg of the samarium and cobalt co-doped bismuth ferrite nanoparticles obtained above, evenly disperse them in 100 ml of 20% by volume methanol aqueous solution, and move them into a sealed reactor. In the sealed reactor, nitrogen is first introduced for 30 minutes to remove the air in the system, and then it is placed under ultrasonic vibration and light conditions. Starting from the 0th hour, the amount of hydrogen generated above the reactor is measured every 1 hour, and the measurement is continued for 4 hours.

[0041] The following test was used to verify the effect of the invention:

[0042] 1. Preparation and characterization of samarium and cobalt co-doped bismuth ferrite nanomaterials

[0043] The crystal phase structures of the prepared samarium and cobalt co-doped bismuth ferrite nanomaterials doped with 10% samarium and 20% cobalt and pure phase bismuth ferrite nanomaterials were characterized by X-ray powder diffraction (XRD). Figure 1 The XRD patterns of samarium and cobalt co-doped bismuth ferrite nanomaterials doped with 10% samarium and 20% cobalt and pure phase bismuth ferrite nanomaterials are shown in the figure, corresponding to the standard card of bismuth ferrite (PDF#01-086-1518). As shown in the figure, the diffraction peaks 2θ=22.4°, 31.8°32.0°, 39.5°, 45.8° and 51.3° of samarium and cobalt co-doped bismuth ferrite nanomaterials doped with 10% samarium and 20% cobalt correspond to the (012), (104), (110), (202), (024) and (116) crystal planes of bismuth ferrite respectively. The XRD diffraction pattern of bismuth ferrite nanomaterials is consistent with the standard card (PDF#01-086-1518), and no other impurities appear in bismuth ferrite, proving that the prepared bismuth ferrite is a standard rhombohedral perovskite structure. The XRD spectrum of samarium and cobalt co-doped bismuth ferrite nanomaterials is basically consistent with bismuth ferrite, and no diffraction peaks of other impurities are found in the spectrum. However, after doping with samarium and cobalt, the double peaks of (104) and (110) crystal planes are transformed into single peaks, and the diffraction peaks are shifted to the right. This is because Sm 3+ The size is smaller than Bi 3+ and Co 3+ ion The size is larger than Fe 3+ Small, according to the Bragg diffraction equation 2dsinθ = n λ It can be seen that the diffraction peak should shift to the right after doping, indicating that the substitution of samarium ions and cobalt ions causes the compression of Fe-O bonds and the effective stretching of Bi-O bonds, and the structural deformity is more obvious. It also proves that samarium ions and cobalt ions are successfully doped into bismuth ferrite. The above results show the successful preparation of samarium and cobalt co-doped bismuth ferrite nanomaterials.

[0044] The morphology of the prepared samarium and cobalt co-doped bismuth ferrite nanomaterials was observed by scanning electron microscopy. Figure 2 As shown, the prepared samarium and cobalt co-doped bismuth ferrite nanomaterial has an irregular square-like flake morphology and an average particle size of about 40 to 160 nm. Compared with bismuth ferrite, the crystal shape does not change much, and the average particle size is slightly reduced after the addition of samarium and cobalt elements.

[0045] The migration and recombination of photogenerated carriers in samarium and cobalt co-doped bismuth ferrite nanomaterials and bismuth ferrite nanomaterials were studied by fluorescence spectroscopy (PL). - and h + Separation efficiency, thereby promoting the generation of active free radicals. Figure 3 As shown, the PL intensity of the samarium and cobalt co-doped bismuth ferrite nanomaterial is significantly lower than that of bismuth ferrite. This fluorescence quenching phenomenon indicates that the prepared samarium and cobalt co-doped bismuth ferrite nanomaterial effectively improves the separation efficiency of photogenerated electrons and holes.

[0046] The absorption characteristics of samarium and cobalt co-doped bismuth ferrite nanomaterials and bismuth ferrite nanomaterials in the visible light range were studied by ultraviolet-visible absorption spectra (UV-vis DRS). Figure 4 As shown in Figure 1, bismuth ferrite nanomaterials exhibit an absorption edge at 560nm due to their inherent narrow band gap. However, compared with bismuth ferrite nanomaterials, the absorption edge of samarium and cobalt co-doped bismuth ferrite nanomaterials shifts to longer wavelengths, and the absorption spectrum gradually red-shifts. The red-shifted optical absorption edge indicates that the utilization efficiency of solar energy is higher than that of bismuth ferrite.

[0047] 2. Study on catalytic degradation efficiency

[0048] The degradation efficiency of samarium and cobalt co-doped bismuth ferrite nanomaterials with different doping ratios for degradation of rhodamine B was compared by ultraviolet spectrophotometer to obtain the doping ratio with the best performance. Figure 5 The catalytic performance comparison of samarium cobalt co-doped bismuth ferrite with different doping ratios under ultrasonic vibration (40kHz) is demonstrated. The experimental results show that samarium and cobalt co-doped bismuth ferrite nanomaterials doped with 10% samarium and 20% cobalt have the best catalytic degradation performance.

[0049] Figure 6 The results show the degradation effects of samarium and cobalt co-doped bismuth ferrite nanomaterials doped with 10% samarium and 20% cobalt, samarium-doped bismuth ferrite doped with 10% samarium, cobalt-doped bismuth ferrite doped with 20% cobalt and pure bismuth ferrite nanomaterials on the organic pollutant rhodamine B in the same time. Specifically, during the 60-minute degradation experiment, samarium and cobalt co-doped bismuth ferrite, samarium-doped bismuth ferrite, cobalt-doped bismuth ferrite and pure bismuth ferrite achieved rhodamine B degradation rates of 82.5%, 36.4%, 39.3% and 13.7%, respectively. At the same time, by comparing the rate constant k value, it can be found that the degradation rate constant k value of samarium and cobalt co-doped bismuth ferrite (0.03046min -1 ) is significantly higher than that of samarium-doped bismuth ferrite (0.0078min -1 ), Cobalt-doped bismuth ferrite (0.00695min -1 ) and bismuth ferrite (0.00212min -1 ), even reaching 14.36 times that of bismuth ferrite. This result shows that in terms of degradation of organic pollutants, samarium and cobalt co-doped bismuth ferrite nanomaterials have higher degradation efficiency and reaction rate.

[0050] 3. Study on hydrogen production performance

[0051] The present invention uses a gas chromatograph to detect the hydrogen production performance of bismuth ferrite and samarium and cobalt co-doped bismuth ferrite nanomaterials under ultrasonic vibration and light irradiation conditions. The experiment was conducted for 4 hours under ultrasonic vibration (40kHz) and xenon lamp irradiation (300W) environment. Figure 7 The results show that the hydrogen production of pure bismuth ferrite nanomaterials in 4 hours is only 3434.4 μmol·g under mechanical vibration (40kHz) and xenon lamp irradiation (300W). -1 In comparison, under the same conditions, the hydrogen production of samarium and cobalt co-doped bismuth ferrite nanomaterials in 4 hours was about 5944.28 μmol·g -1 , which is about 1.73 times the hydrogen production of pure bismuth ferrite nanomaterials. This result fully demonstrates that samarium and cobalt co-doped bismuth ferrite nanomaterials have significant advantages in hydrogen production efficiency.

[0052] In summary, the present invention successfully synthesized samarium and cobalt co-doped bismuth ferrite nanomaterials by coprecipitation method, using bismuth nitrate, iron nitrate, samarium nitrate and cobalt nitrate as reactants. The experimental results show that samarium and cobalt co-doped bismuth ferrite nanomaterials show significant improvement in piezoelectric photocatalytic degradation and hydrogen production performance. This method of using mechanical energy and natural light for piezoelectric photocatalytic degradation of organic pollutants and decomposition of water to produce hydrogen has the characteristics of simple process flow and strong operability, indicating broad application prospects.

Claims

1. Preparation of samarium and cobalt co-doped bismuth ferrite nanomaterials and their piezoelectric photocatalytic application, characterized in that The preparation method and application have the following steps: Step 1: dissolving bismuth nitrate, iron nitrate, samarium nitrate and cobalt nitrate in a dilute nitric acid solution, and ultrasonicating to form a uniform transparent colorless solution; then adjusting the pH value to make the solution alkaline, centrifuging the solution to obtain a precipitate, and drying to obtain a certain amount of solid; Step 2: Grind the solid obtained in step 1, and place the ground powder into a tube furnace for calcination in air to obtain a calcined solid powder; Step 3, the solid powder calcined in step 2 is acid-washed and water-washed, centrifuged, alternately three times, and finally washed with ethanol, and vacuum-dried to obtain samarium and cobalt co-doped bismuth ferrite nanoparticles; Step 4: Application of samarium and cobalt co-doped bismuth ferrite nanomaterials in piezoelectric-photosynergistic catalytic degradation of organic pollutants, the specific method is: uniformly dispersing the samarium and cobalt co-doped bismuth ferrite nanomaterials in a rhodamine B aqueous solution, measuring the absorbance change of the rhodamine B aqueous solution by a liquid ultraviolet-visible spectrophotometer under the conditions of mechanical force and light, and finally calculating the degradation rate of the rhodamine B aqueous solution; Step 5. Application of samarium and cobalt co-doped bismuth ferrite nanomaterials in piezoelectric-photocatalytic decomposition of water to produce hydrogen. The specific method is: uniformly disperse the samarium and cobalt co-doped bismuth ferrite nanomaterials in a methanol-water solution, introduce N2 to remove oxygen, and then measure the amount of hydrogen produced by gas chromatography under the action of mechanical force and light.

2. The method according to claim 1, characterized in that: In step 1, the molar ratio of bismuth nitrate to samarium nitrate is 0.8:0.1 to 0.95:0.05, and the molar ratio of iron nitrate to cobalt nitrate is 0.8:0.1 to 0.95:0.05; The dilute nitric acid solution in step 1 is prepared by mixing concentrated nitric acid with water in a volume ratio of 1:30 to 40; The pH value in step 1 is alkaline at 9 to 10; The drying conditions in step 1 are: temperature of 50-70°C and time of 9-14h.

3. The method according to claim 1, characterized in that: In step 2, the heating rate is 4-8°C / min; The calcination temperature in step 2 is first raised to 300° C. and maintained for 30 to 60 minutes, and then raised to 500° C. and maintained for 40 to 120 minutes.

4. The method according to claim 1, characterized in that: The centrifugal speed in step 3 is 9000 r / min; The vacuum drying conditions described in step 3 are: temperature of 50 to 70° C., vacuum degree of -25 to -30 kPa, and time of 9 to 14 h.

5. The method according to claim 1, characterized in that: The mechanical force and light in steps 4 and 5 are generated by ultrasound and xenon lamp irradiation, wherein the ultrasound frequency is 20-60 kHz, the xenon lamp power is 100-500 W, and the filter is λ>420 nm; The concentration of the Rhodamine B (RhB) solution in step 4 is 5 mg / L; The volume fraction of the methanol aqueous solution in step 5 is 5%-30%.

6. A samarium and cobalt co-doped bismuth ferrite nanomaterial prepared by the method of claims 1 to 4.

7. The samarium and cobalt co-doped bismuth ferrite nanomaterial according to claim 1 has significantly improved performance compared with pure bismuth ferrite nanomaterials in the applications of piezoelectric-photosynergistic degradation of rhodamine B and piezoelectric-photodecomposition of water to produce hydrogen. The degradation rate constant is 14.36 times that of pure bismuth ferrite, and the hydrogen production efficiency is 1.73 times that of pure bismuth ferrite.